Genetic diversity and phylogenetic analysis of Indonesian local and commercial rabbit breeds based on mitochondrial D-loop - Lestari, D. A.; Latifa, A. P.; Sutopo, S.; Kurnianto, E.; Setiatin, E. T.; Agustine, A. D.; Nabilah, Z.; Kamila, F. T.; Prahara, P. G.; Kamalludin, M. H.; Setiaji, A. (Journal of the Indonesian Tropical Animal Agriculture, 2025)
This study aimed to evaluate the genetic diversity and phylogenetic relationships among four rab-bit breeds raised in Central Java, namely Indonesian Local rabbit (LC), Hycole (HC), Hyla (HL), and New Zealand White (NZ), using mitochondrial D-loop region sequences. A total of 40 blood samples were collected from rabbits in three regencies in Central Java. DNA was extracted from each sample, followed by gene amplification, Sanger sequencing, and sequence analysis. A 906 bp fragment of the mitochondrial D-loop region was successfully amplified from all individuals. The overall genetic di-versity was found to be low, with mean values of k = 4.615, nucleotide diversity (π) = 0.00509 ±0.00092, and haplotype diversity (Hd) = 0.385 ± 0.070. Genetic distance analysis showed a close rela-tionship among the breeds, ranging from 0.00349 to 0.00610. Two haplotypes (A and B) were identi-fied, and both were shared across all breeds, indicating limited genetic differentiation. Phylogenetic tree reconstruction further demonstrated that the four breeds clustered closely together and were most likely derived from European lineages rather than distinct indigenous origins. In conclusion, rabbits raised in Central Java represent a genetically homogenous group with low diversity, highlighting the need for broader genetic resource management and conservation strategies to ensure long-term popula-tion sustainability.